Increasing Knowledge and Understanding of Social Cognitive Career Theory for Employees of PT BPR Artha Tanah Mas - Constantinus Constantinus; Lisa Ardaniyati; Hermiana Vereswati (Universitas 45 Surabaya, 2022)
Social Cognitive Career Theory (SCCT) which pays attention to employee interest in career development is not known and understood by employees and management of the Limited Company of Rural Banking (PT BPR) Artha Tanah Mas. Employees whose careers will be developed are not enthusiastic because the development is not in accordance with their interests. The purpose of this community service is to increase knowledge and understanding of Social Cognitive Career Theory for employees and management of PT BPR Artha Tanah Mas. The method used was in the form of lectures, questions and answers, sharing, assignments, and games which were carried out on October 1, 2022 at the PT BPR Artha Tanah Mas Office in Semarang City, attended by all staff employees, supervisors and managers. The pre-test was given before the training, and the post-test was given after the training. The test results using the Wilcoxon test statistical technique showed that the knowledge and understanding of the participants after the training increased significantly compared to the knowledge and understanding of the participants before the training. Thus the purpose of community service in the form of training has been achieved.